Constrained stochastic data sampling for deep learning–based time-lapse hydraulic tomography under reactive-induced permeability evolution - Zi-Yan Chou; Jui-Pin Tsai; Bo-Tsen Wang; Chia-Hao Chang; Ying-Fan Lin; Tian-Chyi Jim Yeh (Journal of Hydrology, 2026)

Myeloid-derived suppressor cells-guided mesoporous silica nanoplatform delivering a BET inhibitor exerts anticancer effects by reprogramming the immunosuppressive tumor microenvironment - Li-Chan Chang; Li Xu; Yin-Fen Liu; Chang-An Lin; Si-Han Wu; Wen-Pin Su (Chemical Engineering Journal, 2026)

Targeting the NOX4/NLRP inflammasome axis confers protection by isoliquiritigenin against H2O2-induced synovial inflammation - Yu-Chun Chang; Wei-Wen Kuo; Yen-Pin Chen; Shih-Wen Kao; Dennis Jine-Yuan Hsieh; Tsung-Jung Ho; Chia-Hua Kuo; Chien-Yao Fu; Chih-Yang Huang; Shinn-Zong Lin (Chemico-Biological Interactions, 2026)

Funnel-bottom smart pond engineering reduces dissolved inorganic nitrogen accumulation in intensive shrimp culture - Hsueh-Han Hsieh; W. Sanjaya Weerakkody; Pin-Chun Liu; Ing-Jer Huang; Chin-Chang Hung (Aquacultural Engineering, 2026)

Aqueous acid washing as an effective pretreatment strategy for crude algal oil refining: Enrichment of fatty matter and reduction of impurities - Camille Zhi Qing P'ng; Mun Yuen Chang; Siti Hanifah Adiiba; Sheau Chien Chee; Noorazlenawati Borhan; Mohammad Ghadaffi Mohd Nor; Tg M. Uzaini Tg Mat; Cher Pin Song; Eng-Seng Chan (Algal Research, 2026)

A comparative study of methods for quantifying sand-sized sediment grain textural parameters - Xiaotian Shen; Xing Jian; Wei Zhang; Ruolan Liao; Dongming Hong; Chao Li; Shaohua Zhao; James T. Liu; Yuan-Pin Chang (Sedimentary Geology, 2026)

Deglacial Laminated Diatom Mats (Ethmodiscus rex), in the Western Philippine Sea and their palaeoceanographic significance - Thilina Munasinghe; Pierrick Fenies; Jyh-Jaan Steven Huang; Ludvig Löwemark; Nathalie Babonneau; Gueorgui Ratzov; Shu-Kun Hsu; Chih-Chieh Su; Maria-Angela Bassetti; Natalia Vazquez Riveiros; Yuan-Pin Chang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Poly(lactic-co-glycolic acid) (PLGA)-based vaccine delivery systems for fish: physicochemical properties, immunological mechanisms, and applications - Shu-Chun Chuang; Yi-Chen Lin; Ya-Shuan Chou; Shang-Pin Liu; Shao-Wen Hung; Ti-Chun Chang; Chung-Hwan Chen; Chung-Da Yang (Fish & Shellfish Immunology, 2026)

The role of purification of enzymatic biodiesel from sludge palm oil in improving fuel properties, storage stability, engine performance, and exhaust gas emissions - Jun Mann Loh; Wail Gourich; Cher Pin Song; Charles R. Sarimuthu; Karthini Nagalingam; Wai Onn Hong; Mun Yuen Chang; Eng-Seng Chan (Biomass and Bioenergy, 2026)

Design and verification of a microbial consortium with an anchoring-interface enhancement strategy for efficient PAHs degradation in groundwater - Wang Kai Tong; Jiajun Hu; Chaomeng Dai; Jia Jie Zou; Han Tang; Piao Yi Jiang; Min-tian Gao; Jixiang Li; Xihua Wang; Yalei Zhang; Ken-Lin Chang; Kah Hon Leong; et al. (Water Research, 2026)

Joint inversion of hydraulic and thermal parameter fields using a CNN-based framework and transient hydraulic tomography - Che-Wei Liang; Jui-Pin Tsai; Zi-Yan Chou; Chia-Hao Chang; Bo-Tsen Wang (Journal of Hydrology, 2026)

Development of an artificial intelligence (AI) marine scientific research model: The case of marine science and technology policy and its legitimate practice in Taiwan - Juei-Cheng Jao; Chiao-Wen Lin; Pin-Chien Chen; Yi-Cheng Chang; Yi-Juen Chen; Wen-Hong Liu (Marine Policy, 2026)

Correction: Impact of the Benguela coastal low-level jet on the southeast tropical Atlantic SST bias in a regional ocean model - Jaison Kurian; Pin Li; Ping Chang; Christina M. Patricola-DiRosario; Justin Small (Climate Dynamics, 2026)

Purinergic ion channel-type P2X7 receptor regulates SK3 channel to promote the progression of gastric cancer - Pin Wan; Chang-bing Wu (Tissue and Cell, 2026)

Targeted degradation of emerging pollutants based on specific recognition and ROS confinement effects of molecularly imprinted cavities - Jun Bo Zhang; Xu Jiang; Chaomeng Dai; Jixiang Li; Jiajun Hu; Min-tian Gao; Xueji You; Hongcheng Zhang; Shunyang Li; Peng Qiu; Zhu Zhu; Xihua Wang; et al. (Chemical Engineering Journal, 2026)

Biomimetic microneedle patch integrating ROS-scavenging nanoceria, anti-inflammatory phytochemical, and macrophage-membrane-coated nanoparticles for local hepatic therapy of endotoxemia - Bingwen Zhu; Chang Sun; Dongrong Luo; Zhongliang Zhang; Linguo Cao; Tao Bi; Aolin Jiang; Yuying Liang; Zehui Jiang; Haihua Luo; Pin Jiang; Shaoqing Liu; et al. (Chemical Engineering Journal, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

Visible light driven highly selective oxidation of HMF coupled with H2 evolution via bimetal-doped synergism on ZnIn2S4 nanosheets - Yachen Hu; Wei Jiang; Zijun Zhang; Qinqin Jiang; Yawen Jiang; Lang Sun; Panjing Xu; Yanling Chang; Chuanqiang Wu; Ziming Fan; Meiling Wang; Zhou Chen; et al. (Chemical Engineering Journal, 2025)

Fungal mycelial pellet as a biosponge for bacterial immobilization: A novel biocarrier for synergistic adsorption-degradation of PAHs - Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Wang Kai Tong; Hong Cheng Zhang; Min-tian Gao; Yalei Zhang; Zhi Li; Kah Hon Leong; Lang Zhou; Ken-Lin Chang; Swee Pin Yeap (Chemical Engineering Journal, 2025)

An investigation of localized entropy driven cathode electrolyte interphase to a one-step complete deprotonation of ethylene carbonate on Ni-rich layered material of lithium-ion battery - Laurien Merinda; Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Chusnul Khotimah; Han-Pin Hsieh; Jeng-Kuei Chang; Shu-Chih Haw; Chih-Wen Pao; Jeng-Lung Chen; Qunjie Xu; et al. (Chemical Engineering Journal, 2025)

Dramatically suppressed climate signals in the Yellow River - Yonggui Yu; Rick J. Yang; Gang Wang; Jaap H. Nienhuis; Xianyao Chen; James T. Liu; Marcel van der Perk; Rens van Beek; Xuefa Shi; Shuqing Qiao; Zhi Li; Jay Lee; et al. (Global and Planetary Change, 2025)

Linking source-to-sink processes, organic matter composition, and oxygen consumption on a shallow passive margin shelf sustained by small mountainous rivers - Yu-Shih Lin; Chih-Lin Wei; Yuan-Pin Chang; Jih-Terng Wang; Shu-Ying Chuang; Liang-Chi Wang; James T. Liu; Hong-Chun Li; Chieh-Wei Hsu (Geochimica et Cosmochimica Acta, 2025)

Automated digital reconstruction of high-fidelity present-day geometries for segmental tunnel linings based on segmented point clouds - Wei Lin; Brian Sheil; Pin Zhang; Jiaqi Chang; Xiongyao Xie (Tunnelling and Underground Space Technology, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Efficient activation of percarbonate by metal-free carbonylated activated carbon for green groundwater remediation: Performance, mechanism, applicability, and environmental implications - Jun Bo Zhang; Yi Yang; Chaomeng Dai; Jixiang Li; Yucang Liang; Jiajun Hu; Min-tian Gao; Xueji You; Xu Jiang; Shunyang Li; Xihua Wang; Zhi Li; et al. (Journal of Hazardous Materials, 2025)

Adverse pulmonary effects and metallic characteristic of size-resolved welding fumes in human lung epithelial BEAS-2B cells - Pin-Hao Qiu; Chia-Hua Lin; Yen-Ping Peng; Ku-Fan Chen; Yi-Chun Chen; Yung-Chang Lin; Chia-Hsiang Lai (Environmental Toxicology and Pharmacology, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Tailoring lignocellulose-derived biochar for peroxymonosulfate-based catalytic environments: Optimizing active sites, revealing activation mechanisms, and advancing groundwater remediation applications - Jun Bo Zhang; Chaomeng Dai; Jiajun Hu; Jixiang Li; Min-tian Gao; Yeap Swee Pin; Kah Hon Leong; Ken-Lin Chang; Xing Song Xu; Xu Jiang (Journal of Hazardous Materials, 2025)

Integrated ultrafiltration-like forward osmosis and nanofiltration for natural rubber skim latex concentration: Dewatering performance, fouling mechanism, and economic analysis - Zhen Hong Chang; Jing Yao Sum; Ebrahim Mahmoudi; Yeit Haan Teow; Swee Pin Yeap; Hafsah Mohd Ghazaly; Anizan Aziz (Chemical Engineering Journal, 2025)

Applications, life cycle assessment, and circular economy of bamboo torrefaction for sustainability: A state-of-the-art review - Wei-Hsin Chen; Pin-Chun Liang; Wei-Yi Wang; Pen-Chi Chiang; Jiří Ryšavý; Jakub Čespiva; Jo-Shu Chang (Bioresource Technology, 2025)

Hydraulic heterogeneity estimation with transient hydraulic tomography and convolutional encoder-decoder neural network - Yu-Kai Chen; Jui-Pin Tsai; Bo-Tsen Wang; Chia-Hao Chang (Stochastic Environmental Research and Risk Assessment, 2025)

Enhanced deep eutectic solvent extraction of phenolic compounds from hawthorn seeds with ultrasonic and resin in-situ adsorption assistance: Process optimization, component analysis, and extraction mechanism - Pengfei Jiao; Xingmei He; Zhihao Zhou; Xuan Wang; Yunrui Zhang; Pin Chang; Xin Zhang; Peng Wang; Pengpeng Yang; Qiuhong Niu (Food Chemistry, 2025)

Mitigating non-point source pollution in tea plantations: SWAT modeling and field validation of slow-release fertilizers - Chia-Chun Ho; Pin-Chih Shih; Li-Chi Chiang; Yi-Xuan Lin; Hsiu-Feng Liu; Wen-Guei Chang; Guan-Zhou Lin (Environmental Monitoring and Assessment, 2025)

Genome-wide identification, expression analysis and transcriptional regulation of major histocompatibility complex class I genes in mandarin fish Siniperca chuatsi - Jing Hou; Min Chang Li; Lu Qi; Wei Hao; Lan Hao Liu; Zhen Gan; Bei Huang; Wen Shu Huang; Li Wang; Li Li; Shan Nan Chen; Pin Nie (Aquaculture, 2025)

Estimating basin-scale heterogeneous hydraulic diffusivity fields based on signal decomposition and river stage tomography - Bo-Tsen Wang; Yu-Li Wang; Chia-Hao Chang; Chin-Tsai Hsiao; Jordi Mahardika Puntu; Ping-Yu Chang; Jui-Pin Tsai (Journal of Hydrology, 2025)

Survival disparities among Asian, Native Hawaiian and Pacific Islander (ANHPI) patients with non-Hodgkin lymphoma (NHL) in the United States - Chun-Pin Esther Chang; Jing Wang; Catherine Lee; Mia Hashibe (Cancer Causes & Control, 2025)

Fault materials and creep characteristics in mudstone areas: A case study of Chegualin Fault in southwestern Taiwan - Pin-Hao Chen; Yen-Hua Chen; Ming-Chih Hsieh; Yan-Wei Huang; Chien-Che Huang; Wei-Teh Jiang; Jey-Jau Lee; Yao-Chang Lee; Hwo-Shuenn Sheu (Engineering Geology, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Establishment of a pseudotargeted LC‒MS/MS workflow for analyzing triglycerides in biological samples - Wei-Chieh Wang; Chin-Yi Wang; Ta-Chen Su; Po-Chih Lin; Wen-Chi Chang; Kuei-Pin Chung; Ching-Hua Kuo (Analytica Chimica Acta, 2025)

Fast screening of COVID-19 inpatient samples by integrating machine learning and label-free SERS methods - Jaya Sitjar; Huey-Pin Tsai; Han Lee; Chun-Wei Chang; Xin-Ni Wu; Jiunn-Der Liao (Analytica Chimica Acta, 2025)

Climate-controlled distribution of erosion over the Himalaya in the late Quaternary: Evidence from Sr-Nd isotope variability in paleo-Yamuna channel sediments - Mohd Amir; Debajyoti Paul; Shouye Yang; Yuan-Pin Chang (Quaternary Science Reviews, 2025)

The difference in roaming behavior between owned and unowned dogs in a satoyama landscape area - Tsung-Han Kuo; Gau-Ming Chang; Pin-Huan Yu; Wei-Hsuan Chen; Shih-Ching Yen (Applied Animal Behaviour Science, 2025)

Intraspecific genetic diversity with unrestricted gene flow in the domoic acid-producing diatom Nitzschia navis-varingica (Bacillariophyceae) from the Western Pacific - Suh Nih Tan; Yuichi Kotaki; Sing Tung Teng; Hong Chang Lim; Chunlei Gao; Nina Lundholm; Matthias Wolf; Haifeng Gu; Po Teen Lim; Chui Pin Leaw (Harmful Algae, 2025)

Sedimentary Signatures of Super Typhoon Haiyan: Insight from Core Record in South China Sea - Yu-Huang Chen; Chih-Chieh Su; Pai-Sen Yu; Ta-Wei Hsu; Sheng-Ting Hsu; Hsing-Chien Juan; Yuan-Pin Chang; Yu-Fang Ma; Shye-Donq Chiu (Journal of Marine Science and Engineering, 2024)
Sedimentary records of event deposits are crucial for regional natural disaster risk assessments and hazard history reconstructions. After Super Typhoon Haiyan passed through the South China Sea in 2013, five gravity cores were collected along the typhoon path in the southern South China Sea basin (>3800 mbsl). The results showed that Super Typhoon Haiyan deposits with clear graded bedding are preserved at the top of all cores. The thickness of the typhoon layers ranges from 20 to 240 cm and is related to changes in typhoon intensity. The lack of river-connected submarine canyon systems limited the transportation of terrestrial sediments from land to sea. Super Typhoon Haiyan-induced large surface waves played an important role in carrying suspended sediment from the Philippines. The Mn-rich layers at the bottom of the typhoon layers may be related to the soil and rock composition of the Palawan region, which experienced tsunami-like storm surges caused by Super Typhoon Haiyan. These Mn-rich layers may serve as a proxy for sediment export from large-scale extreme terrigenous events. This study provides the first sedimentary record of extreme typhoon events in the deep ocean, which may shed light on reconstructing regional hazard history.

Peteryoungia algae sp. nov. isolated from seaweeds of Gouqi Island, China, and its unique genetic features among Peteryoungia strains - Jun Yin; Min He; Xiao-Xiao Liu; Chang-Bin Ren; Hou-Hong Liu; Hai Luo; Gen Chen; Ze-Fei Wang; Sanjit Chandra Debnath; Pin-Mei Wang; Hai-Xin Chen; Dao-Qiong Zheng (Antonie van Leeuwenhoek, 2024)

Coral mariculture using abandoned abalone farming ponds in northeastern Taiwan - Shinya Shikina; Yin-Chu Cheng; Tzu-Chieh Lin; Yu-En Chang; Pin-Hsuan Tsai; Emma Chen; Yu-Chuan Chang; Yuen-Yi Leung; Yi-Chun Yu; Yi-Ling Chiu (Aquaculture, 2024)

Treatment of arsenic-contaminated groundwater with a novel iron oxide/carbon composite as the adsorbent - Hung-Hsiang Chen; Yu-Chen Chang; Wei-Kuo Wei; Yung-Pin Tsai; Chih-Chi Yang; Ku-Fan Chen (Water, Air, & Soil Pollution, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

MicroRNA dynamics in irisin-mediated signaling pathways within adipose tissue - Ming-Yun Ho; Kai-Pin Chiu; Ming-Lung Tsai; Jih-Kai Yeh; Yi-Chun Huang; Yan-Rong Li; Horng-Dar Wang; I-Chang Hsieh; Ming-Shien Wen; Chao-Yung Wang (Journal of Biosciences, 2024)

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

Characterization and Genomic Analysis of Affinirhizobium gouqiense sp. nov. Isolated from Seawater of Gouqi Island Located in the East China Sea and Reclassification of Rhizobium lemnae to the Genus Affinirhizobium as Affinirhizobium lemnae comb. nov. - Min He; Gen Chen; Ke-Jing Li; Xing-Xing Tang; Xiao-Xiao Liu; Chang-Bin Ren; Hou-Hong Liu; Hai Luo; Sanjit Chandra Debnath; Pin-Mei Wang; Hai-Xin Chen; Dao-Qiong Zheng (Current Microbiology, 2024)

Omics analysis of ‘Shine Muscat’ grape grafted on different rootstocks in response to cadmium stress - Yafeng Gu; Xiaobin Fan; Ke Jiang; Pin Liu; Huiqing Chang; Okbagaber Andom; Jieshan Cheng; Zhaojun Li (Science of The Total Environment, 2024)

Wildfire-vegetation-climate-human interactions in the central Taiwan region during 17.3–2.0 cal kyr BP, inferred from sediments of Toushe Basin - Abdur Rahman; Yuan-Pin Chang; Hong-Chun Li; Ling-Ho Chung; Yu-Min Chou; Liang-Chi Wang (Quaternary Science Reviews, 2024)

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

Climate-regulation of organic carbon export in erosive mountain settings: A case study from Taiwan since the last glacial maximum - Li-Wei Zheng; Robert G. Hilton; Yuan-Pin Chang; Rick J. Yang; Xiaodong Ding; Xufeng Zheng; Tsung-Yu Lee; Hsi-Jih Lu; Jung-Tai Lu; Yu-Shih Lin; James T. Liu; Shuh-Ji Kao (Quaternary Science Reviews, 2024)

Postvaccination serosurveillance of foot-and-mouth disease through virus-neutralizing and nonstructural protein antibody tests on pig farms in Taiwan: 2009–2020 - Ming-Chang Lee; Yu-Fen Sun; Ming-Chung Deng; Nien-Nung Lin; Jung-Pin Hsu; Chwei-Jang Chiou; Wen-Jane Tu; Shih-Ping Chen (Preventive Veterinary Medicine, 2024)

Late Holocene paleoclimate reconstruction of northern Taiwan using a multiproxy approach in the Dream Lake sediment core - Abdur Rahman; Wei-Cheng Chang; Kaoru Kashima; Yu Fukumoto; Jyh-Jaan Steven Huang; Ludvig Löwemark; Liang-Chi Wang; Yuan-Pin Chang (Quaternary International, 2024)

Mo, N co-doped cobalt hydroxide nanosheets for highly selective methanol-to-formate electrocatalytic conversion - Yaoxin Wu; Lili Ban; Hanzhen Wang; Qian Yang; Yaao Li; Ke Lu; Yuxiang Li; Pin Cui; Jinfeng Yang; Dalei Chang; Dezheng Yang; Feng Yu; et al. (Chemical Engineering Journal, 2024)

The health risk reduction of PM2.5 via a green curtain system in Taiwan - Yi Hsing Chang; Ting-Hsuan Chen; Hsin-Ying Chung; Hsi-Yu Hsiao; Pin-Chieh Tseng; Yu-Chun Wang; Shih-Chun Candice Lung; Huey-Jen Su; Yaw-Shyan Tsay (Building and Environment, 2024)

Biogeochemistry of sedimentary organic matter in the Yongjiang River estuary in the southern part of Hangzhou Bay, China, since the Late Pleistocene - Dongqin Huang; Xiaolong Li; Zilong Li; Pei Sun Loh; Jianxiong Hu; Jianfang Chen; Yuan-Pin Chang; Chin-Wen Yang; Qin Gao (Journal of Oceanology and Limnology, 2024)

Corrigendum to “Effects of blue space exposure in urban and natural environments on psychological and physiological responses: A within-subject experiment” [Urban For. Urban Green. 87 (2023) 1–9/128066] - Jie Yin; Jittakon Ramanpong; Jin Chang; Chih-Da Wu; Pei-Hua Chao; Chia-Pin Yu (Urban Forestry & Urban Greening, 2024)

The SMAC mimetic GDC-0152 is a direct ABCB1-ATPase activity modulator and BIRC5 expression suppressor in cancer cells - I-Li Lin; Yu-Ting Lin; Yung-Chieh Chang; Sree Karani Kondapuram; Kai-Hsuan Lin; Pin-Chen Chen; Chung-Ying Kuo; Mohane Selvaraj Coumar; Chun Hei Antonio Cheung (Toxicology and Applied Pharmacology, 2024)

Indian summer monsoon variability during the past ~75 ka based on stable isotope records of sediments from NW India - Mohd Amir; Debajyoti Paul; Yuan-Pin Chang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The employment of self-awareness in investigating public willingness to implement low-carbon: The application of labeling theory - Kuei-Feng Chang; I-Tung Shih; Pin-Huan Wang (Journal of Cleaner Production, 2024)

Do greenness and landscape indices for greenspace correlate with suicide ratio? - Hsiao-Yun Lee; Hao-Ting Chang; Samuel Herianto; Chi-Shin Wu; Wan-Yu Liu; Chia-Pin Yu; Wen-Chi Pan; Chih-Da Wu (Landscape and Urban Planning, 2024)

Normal fault evolution in the Penghu Basin, a Paleogene Rift Basin in Western Taiwan Strait: A test of fault growth models - Pin-Rong Wu; Kenn-Ming Yang; Pin-Chi Wang; Chang-Jie Lee; Jong-Chang Wu (Tectonophysics, 2023)

The impact of air pollution on respiratory diseases in an era of climate change: A review of the current evidence - Huan Minh Tran; Feng-Jen Tsai; Yueh-Lun Lee; Jer-Hwa Chang; Li-Te Chang; Ta-Yuan Chang; Kian Fan Chung; Han-Pin Kuo; Kang-Yun Lee; Kai-Jen Chuang; Hsiao-Chi Chuang (Science of The Total Environment, 2023)

Effects of blue space exposure in urban and natural environments on psychological and physiological responses: A within-subject experiment - Jie Yin; Jittakon Ramanpong; Jin Chang; Chih-Da Wu; Pei-Hua Chao; Chia-Pin Yu (Urban Forestry & Urban Greening, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Coupling gas purging with inorganic carbon supply to enhance biohydrogen production with Clostridium thermocellum - Changman Kim; Isaac Wolf; Chang Dou; Lauren Magnusson; Pin-Ching Maness; Katherine J. Chou; Steven Singer; Eric Sundstrom (Chemical Engineering Journal, 2023)

Human Papillomavirus Vaccination Knowledge, Barriers, and Recommendations Among Healthcare Provider Groups in the Western United States - Shauna Ayres; Alexandra Gee; Seungmin Kim; Mia Hashibe; Aisha Praag; Danielle Kaiser; Chun-Pin Chang; Heather M. Brandt; Deanna Kepka (Journal of Cancer Education, 2022)

When conventional methods fall short: identification of invasive cryptic Golden Apple Snails (Pomacea canaliculata; P. maculata) using environmental DNA - Pritam Banerjee; Kathryn A. Stewart; Gobinda Dey; Raju Kumar Sharma; Jyoti Prakash Maity; Michael W. Y. Chan; Kuo Pin Chang; Tsung-Hsien Chen; Chia-Ti Hsu; Chien-Yen Chen (Hydrobiologia, 2022)

Integrating AIS, GIS and E-Chart to Analyze the Shipping Traffic and Marine Accidents at the Kaohsiung Port - Chien-Chang Chou; Chia-Nan Wang; Hsien-Pin Hsu; Ji-Feng Ding; Wen-Jui Tseng; Chien-Yi Yeh (Journal of Marine Science and Engineering, 2022)
In the past, case study and questionnaire survey methodologies have often been used to analyze the causes of marine accidents. One of the disadvantages of these two methods is that they can only interpret the specific causes of one particular marine accident at a time. They cannot analyze and find the common causes of most marine accidents. Therefore, this study integrates the Automatic Identification System, Geographic Information System, and an e-chart to explore the relationship between environmental factors (wind, wave, tide, and current), locations, and significant common causes of marine accidents. Firstly, an Automatic Identification System is used to collect the traffic flows of vessels entering/exiting the port. The locations of maritime accidents were then plotted on an e-chart, after which we can quickly analyze the locations of marine accidents on the e-chart. Furthermore, environmental data are displayed using Geographic Information System. Subsequently, all data, including traffic flows of vessels, locations of marine accidents, and environmental data, are integrated into the e-chart simultaneously. As a result, the information related to factors affecting the probability of marine accidents could be displayed clearly on the e-chart. Finally, findings and conclusions are given to port authorities to help manage the ship traffic flow and reduce the probability of the occurrence of marine accidents around the port efficiently.

Importance of surface charge of soot nanoparticles in determining inhalation toxicity in mice - Ta-Chih Hsiao; Chia-Li Han; Tzu-Ting Yang; Yueh-Lun Lee; Yu-Fang Shen; Yu-Teng Jheng; Chii-Hong Lee; Jer-Hwa Chang; Kian Fan Chung; Han-Pin Kuo; Hsiao-Chi Chuang (Environmental Science and Pollution Research, 2022)

Correction to: Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Paleolimnological evidence for lacustrine environmental evolution and paleo-typhoon records during the late Holocene in eastern Taiwan - Liang-Chi Wang; Yu-Min Chou; Huei-Fen Chen; Yuan-Pin Chang; Hong-Wei Chiang; Tien-Nan Yang; Liang-Jian Shiau; Yue-Gau Chen (Journal of Paleolimnology, 2022)

Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Impact of the Benguela coastal low-level jet on the southeast tropical Atlantic SST bias in a regional ocean model - Jaison Kurian; Pin Li; Ping Chang; Christina M. Patricola-DiRosario; Justin Small (Climate Dynamics, 2021)

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

Differential time-lag effects of ambient PM2.5 and PM2.5-bound PAHs on asthma emergency department visits - Shih-Chang Hsu; Jer-Hwa Chang; Chon-Lin Lee; Wen-Cheng Huang; Yuan-Pin Hsu; Chung-Te Liu; Shio-Shin Jean; Shau-Ku Huang; Chin-Wang Hsu (Environmental Science and Pollution Research, 2020)

Associations of soluble metals and lung and liver toxicity in mice induced by fine particulate matter originating from a petrochemical complex - Hsiao-Chi Chuang; Ruei-Hao Shie; Chii-Hong Lee; Chia-Pin Chio; Tzu-Hsuen Yuan; Jui-Huan Lee; Chang-Chuan Chan (Environmental Science and Pollution Research, 2020)

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Calycosin Preserves BDNF/TrkB Signaling and Reduces Post-Stroke Neurological Injury after Cerebral Ischemia by Reducing Accumulation of Hypertrophic and TNF-α-Containing Microglia in Rats - Chien-Chin Hsu; Ting-Wei Kuo; Wen-Pin Liu; Ching-Ping Chang; Hung-Jung Lin (Journal of Neuroimmune Pharmacology, 2020)

Development of a Direction-Oriented Motion and Short-Sitting and Lying Tai Chi (DOM-SSLTC) Model for Function Recovery in Stroke Patients - Lian-Hui Lee; Hwai-Ting Lin; Nai-Wen Tsai; Yung-Chieh Yen; Cheng-Hsien Lu; Chun-Chung Lui; Hsien-Ming Chung; Kun-Chang Tsai; Shih-Pin Hsu; Huan-Wen Tsui (Journal of Medical and Biological Engineering, 2019)

Survey of lead concentration in tap water on a university campus - Fu-Chun Chang; Yi-Pin Lin (Environmental Science and Pollution Research, 2019)

Zircon trace elements and magma fertility: insights from porphyry (-skarn) Mo deposits in NE China - Qihai Shu; Zhaoshan Chang; Yong Lai; Xinlu Hu; Huaying Wu; Yong Zhang; Pin Wang; Degao Zhai; Cheng Zhang (Mineralium Deposita, 2019)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Anti-Oxidative Effects of Melatonin Receptor Agonist and Omega-3 Polyunsaturated Fatty Acids in Neuronal SH-SY5Y Cells: Deciphering Synergic Effects on Anti-Depressant Mechanisms - Senthil Kumaran Satyanarayanan; Yin-Hwa Shih; Yu-Chuan Chien; Shih-Yi Huang; Piotr Gałecki; Siegfried Kasper; Jane Pei-Chen Chang; Kuan-Pin Su (Molecular Neurobiology, 2018)

Subcellular Parkinson’s Disease-Specific Alpha-Synuclein Species Show Altered Behavior in Neurodegeneration - Rashed Abdullah; Ketan S. Patil; Benjamin Rosen; Ramavati Pal; Shubhangi Prabhudesai; Sungsu Lee; Indranil Basak; Esthelle Hoedt; Peter Yang; Keith Panick; Hsin-Pin Ho; Emmanuel Chang; et al. (Molecular Neurobiology, 2017)

Effects of liquid layers and distribution patterns on three-phase saturation and relative permeability relationships: a micromodel study - Jui-Pin Tsai; Liang-Cheng Chang; Shao-Yiu Hsu; Hsin-Yu Shan (Environmental Science and Pollution Research, 2017)

Regulation of fine particulate matter (PM2.5) in the Pacific Rim: perspectives from the APRU Global Health Program - Chang-Fu Wu; Alistair Woodward; Ya-Ru Li; Haidong Kan; Rajasekhar Balasubramanian; Mohd Talib Latif; Mazrura Sahani; Tsun-Jen Cheng; Chia-Pin Chio; Nutta Taneepanichskul; Ho Kim; Chang-Chuan Chan; et al. (Air Quality, Atmosphere & Health, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Imaging Rainfall Infiltration Processes with the Time-Lapse Electrical Resistivity Imaging Method - Gang Zhang; Gui-Bin Zhang; Chien-chih Chen; Ping-Yu Chang; Tzu-Pin Wang; Horng-Yuan Yen; Jia-Jyun Dong; Chuen-Fa Ni; Su-Chin Chen; Chao-Wei Chen; Zheng-yuan Jia (Pure and Applied Geophysics, 2016)

Prevalence of potential nitrogen‐fixing, green sulfur bacteria in the skeleton of reef‐building coral I sopora palifera - Shan‐Hua Yang; Sonny T. M. Lee; Chang‐Rung Huang; Ching‐Hung Tseng; Pei‐Wen Chiang; Chung‐Pin Chen; Hsing‐Ju Chen; Sen‐Lin Tang (Limnology and Oceanography, 2016)
Microbial endoliths, which inhabit interior pores of rocks, skeletons and coral, are ubiquitous in terrestrial and marine environments. In this study, various colored layers stratified the endolithic environment within the skeleton of Isopora palifera ; however, there was a distinct green‐pigmented layer in the skeleton (beneath the living coral tissue). To characterize diversity of endolithic microorganisms, 16S ribosomal RNA gene amplicon pyrosequencing was used to investigate bacterial communities in the green layer of eight I. palifera coral colonies retrieved from two locations on Green Island, Taiwan. The dominant bacterial group in the green layer belonged to the bacterial phylum Chlorobi, green sulfur bacteria capable of anoxygenic photosynthesis and nitrogen fixation. Specifically, bacteria of the genus Prosthecochloris were dominant in this green layer. To our knowledge, this is the first study to provide a detailed profile of endolithic bacteria in coral and to determine the prevalence of Prosthecochloris in the green layer. Based on our findings, we infer that these bacteria may have an important functional role in the coral holobiont in the nutrient‐limited coral reef ecosystem.

Population pharmacokinetics of vancomycin in adult Chinese patients with post-craniotomy meningitis and its application in individualised dosage regimens - Wei-wei Lin; Wei Wu; Zheng Jiao; Rong-fang Lin; Chang-zhen Jiang; Pin-fang Huang; Yi-wei Liu; Chang-lian Wang (European Journal of Clinical Pharmacology, 2016)

Pseudo-nitzschia species (Bacillariophyceae) identification and delineation using mitochondrial cox1 gene sequences as compared to LSU rDNA - Suh Nih Tan; Hong Chang Lim; Sing Tung Teng; Po Teen Lim; Chui Pin Leaw (Fisheries Science, 2015)

The assessment of high recharge areas using DO indicators and recharge potential analysis: a case study of Taiwan’s Pingtung plain - Jui-Pin Tsai; Yu-Wen Chen; Liang-Cheng Chang; Wen-Fu Chen; Chung-Jung Chiang; You-Cheng Chen (Stochastic Environmental Research and Risk Assessment, 2015)

The versatile roles of CARDs in regulating apoptosis, inflammation, and NF-κB signaling - Wen-Pin Kao; Chao-Yu Yang; Tsung-Wei Su; Yin-Ting Wang; Yu-Chih Lo; Su-Chang Lin (Apoptosis, 2015)

Predicting 3D pose in partially overlapped X-ray images of knee prostheses using model-based Roentgen stereophotogrammetric analysis (RSA) - Chi-Pin Hsu; Shang-Chih Lin; Kao-Shang Shih; Chang-Hung Huang; Chian-Her Lee (Medical & Biological Engineering & Computing, 2014)

Development of a loop-mediated isothermal amplification method for rapid detection of pigeon circovirus - Shinn Shyong Tsai; Yeng Ling Chang; Yen Li Huang; Hung Jen Liu; Guan Ming Ke; Chwei Jang Chiou; Yao Ching Hsieh; Tsung Chou Chang; Li Ting Cheng; Kuo Pin Chuang (Archives of Virology, 2014)

Genetic variations in TP53 binding sites are predictors of clinical outcomes in prostate cancer patients - Victor C. Lin; Chao-Yuan Huang; Yung-Chin Lee; Chia-Cheng Yu; Ta-Yuan Chang; Te-Ling Lu; Shu-Pin Huang; Bo-Ying Bao (Archives of Toxicology, 2014)

Telbivudine and adefovir combination therapy for patients with chronic lamivudine-resistant hepatitis B virus infections - Ming-Tsung Lin; Yeh-Pin Chou; Tsung-Hui Hu; Hsien-Chung Yu; Yu-Chun Hsu; Ming-Chao Tsai; Po-Lin Tseng; Kuo-Chin Chang; Yi-Hao Yen; King-Wah Chiu (Archives of Virology, 2014)

A study of earthquake inter-occurrence times distribution models in Taiwan - Chi-Hsuan Chen; Jui-Pin Wang; Yih-Min Wu; Chung-Han Chan; Chien-Hsin Chang (Natural Hazards, 2013)

Improvement of a drainage system for flood management with assessment of the potential effects of climate change - Hsiang-Kuan Chang; Yih-Chi Tan; Jihn-Sung Lai; Tsung-Yi Pan; Tzu-Ming Liu; Ching-Pin Tung (Hydrological Sciences Journal, 2013)

The use of allelic imbalance to ascertain cis-regulation for human UGT2B7 in vivo - Pin-Yi Wang; Dezheng Huo; Chang Sun; Olufunmilayo I. Olopade (European Journal of Clinical Pharmacology, 2013)

Assessment of seismic hazard associated with the Meishan fault in Central Taiwan - Jui-Pin Wang; Duruo Huang; Su-Chin Chang (Bulletin of Engineering Geology and the Environment, 2013)

Cordyceps sinensis protects against renal ischemia/reperfusion injury in rats - Hua-Pin Wang; Ching-Wen Liu; Hsueh-Wen Chang; Jen-Wei Tsai; Ya-Zhu Sung; Li-Ching Chang (Molecular Biology Reports, 2013)

Promising outcomes in glutaric aciduria type I patients detected by newborn screening - Chee-Seng Lee; Yin-Hsiu Chien; Shinn-Forng Peng; Pin-Wen Cheng; Lih-Maan Chang; Ai-Chu Huang; Wuh-Liang Hwu; Ni-Chung Lee (Metabolic Brain Disease, 2013)

Genetic diversity of Pseudo-nitzschia brasiliana (Bacillariophyceae) from Malaysia - Hong-Chang Lim; Po-Teen Lim; Suriyanti Nyun-Pau Su; Sing-Tung Teng; Chui-Pin Leaw (Journal of Applied Phycology, 2012)

Reconstruction of oceanographic changes based on diatom records of the core MD012380 since Marine Isotopic Stage 11 in the Banda Sea - Yuan‐Pin Chang; Chung‐Ching Liao; Wei‐Lung Wang (Journal of Quaternary Science, 2012)
Current surface production in the Banda Sea is primarily controlled by monsoonal forcing, the strength of the Indonesian throughflow and surface salinity, and is sensitive to global climate changes. Therefore, variations of paleoproductivity represented by the abundance of diatoms are estimated to assist in understanding possible hydrological changes during glacial–interglacial cycles since Marine Isotopic Stage 11 (MIS 11). During the interglacials, the enhanced austral winter monsoon (southeast monsoon) encourages deepening of the mixed layer and uplifting of the thermocline, thereby increasing surface production. However, accompanied enhancement of the Indonesian throughflow (ITF) within the interglacials brings warm and less‐saline water from the central part of the warm pool water entering the Banda Sea to mitigate development of the upwelling system. Conversely, cooling of the Northern Hemisphere forces the strengthening of the austral summer monsoon (northwest monsoon) to depress the upwelling and reduce production during glacial intervals, whereas the weakening flow of the ITF reduces the influence of low‐salinity capping effects and benefits production. Higher abundance of Chaetoceros sp., dominant in upwelling environments, observed in glacials suggests that strength of the ITF is the most important factor in controlling the vertical thermostructure of the Banda Sea. Copyright © 2012 John Wiley & Sons, Ltd.

PGA distributions and seismic hazard evaluations in three cities in Taiwan - Jui-Pin Wang; Su-Chin Chang; Yih-Min Wu; Yun Xu (Natural Hazards, 2012)

Identification of furo[3′, 2′:3,4]naphtho[1,2-d]imidazole derivatives as orally active and selective inhibitors of microsomal prostaglandin E2 synthase-1 (mPGES-1) - Chih-Hua Tseng; Cherng-Chyi Tzeng; Pin-Keng Shih; Chia-Ning Yang; You-Chung Chuang; Shin-I Peng; Chang-Sheng Lin; Jih-Pyang Wang; Chih-Mei Cheng; Yeh-Long Chen (Molecular Diversity, 2012)

Estimation of nested spatial patterns and seasonal variation in the longitudinal distribution of Sicyopterus japonicus in the Datuan Stream, Taiwan by using geostatistical methods - Yu-Pin Lin; Cheng-Long Wang; Chi-Ru Chang; Hsiao-Hsuan Yu (Environmental Monitoring and Assessment, 2011)

Development and application of RAPD-SCAR markers to identify intra-species hybrids of industrial Saccharomyces cerevisiae - Pin-Mei Wang; Xue-Chang Wu; Xiao-Qin Chi; Yu-Dong Li; Dao-Qiong Zheng; Rui Ding; Hang Min (World Journal of Microbiology and Biotechnology, 2011)

Typhoon Disturbance and Forest Dynamics: Lessons from a Northwest Pacific Subtropical Forest - Teng-Chiu Lin; Steven P. Hamburg; Kuo-Chuan Lin; Lih-Jih Wang; Chung-Te Chang; Yue-Joe Hsia; Matthew A. Vadeboncoeur; Cathy M. Mabry McMullen; Chiung-Pin Liu (Ecosystems, 2011)

Using a hybrid approach to optimize experimental network design for aquifer parameter identification - Liang-Cheng Chang; Hone-Jay Chu; Yu-Pin Lin; Yu-Wen Chen (Environmental Monitoring and Assessment, 2010)

Application of System Dynamics on Shallow Multipurpose Artificial Lakes: A Case Study of Detention Pond at Tainan, Taiwan - Hone-Jay Chu; Liang-Cheng Chang; Yu-Pin Lin; Yung-Chieh Wang; Yu-Wen Chen (Environmental Modeling & Assessment, 2010)

Two genetic divergence centers revealed by chloroplastic DNA variation in populations of Cinnamomum kanehirae Hay - Dai-Chang Kuo; Chia-Chia Lin; Kuo-Chieh Ho; Yu-Pin Cheng; Shih-Ying Hwang; Tsan-Piao Lin (Conservation Genetics, 2010)

Joint Impact of Scaling and Hysteresis on NAPL Flow Simulation - Hung-Hui Chen; Liang-Cheng Chang; Hsin-Yu Shan; Jui-Pin Tsai (Environmental Modeling & Assessment, 2009)

The last 100 000 years' palaeoenvironmental changes inferred from the diatom assemblages of core MD012404 from the Okinawa Trough, East China Sea - Yuan‐Pin Chang; Wei‐Lung Wang; Min‐Te Chen (Journal of Quaternary Science, 2009)
The diatom assemblage records preserved in a sedimentary core MD012404 retrieved from the Okinawa Trough in the East China Sea (ECS) imply palaeoenvironmental changes of the last 100 ka. Our statistical analyses of diatom species abundance data indicate that the assemblages dominate open ocean and warm water, coastal water and freshwater masses in the ECS. These proxy species were used to infer the long‐term variation in surface hydrological conditions and palaeoclimate. Cycles of ca. 23 ka observed in the relative abundance of the tychopelagic species Paralia sulcata indicate that the increases in precipitation driven by solar insolation might have controlled the diatom assemblages in the ECS. The diatom records also indicate relatively low abundances of tropical, tychopelagic and freshwater species during millennial‐scale cold events such as the Younger Dryas and Heinrich events, which have been well expressed in the high‐latitude Northern Hemisphere climate. The floral patterns are interpreted as synchronous cooling and more saline sea surface conditions in the ECS caused by the enhanced Asian winter monsoon during the Northern Hemisphere cold events. The higher abundances of tropical species during deglaciation and the Holocene might have been linked to gradual increases in the inflow of the Kuroshio into the Okinawa Trough. The records also suggest a temporary reduction in tropical species from 5 to 3 ka, corresponding to the Pulleniatina Minimum Event during which the warm‐water planktic foraminifer Pulleniatina obliquiloculata was rare. Copyright © 2009 John Wiley & Sons, Ltd.

Effects of cyanobacterial toxin microcystin-LR on the transcription levels of immune-related genes in grass carp Ctenopharyngodon idella - Lili Wei; Baojian Sun; MingXian Chang; Yi Liu; Pin Nie (Environmental Biology of Fishes, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Identification of an additional two-cysteine containing type I interferon in rainbow trout Oncorhynchus mykiss provides evidence of a major gene duplication event within this gene family in teleosts - Mingxian Chang; Pin Nie; Bertrand Collet; Christopher J. Secombes; Jun Zou (Immunogenetics, 2009)

Fruit ripening-related expression of a gene encoding group 5 late embryogenesis abundant protein inCitrus - Oh-Sung Jeon; Chan-Shick Kim; Sam-Pin Lee; Sung Ku Kang; Chang-Myung Kim; Bong-Gyoon Kang; Yoonkang Hur; In-Jung Kim (Journal of Plant Biology, 2006)

Gene structure and transcription of IRF-2 in the mandarin fish Siniperca chuatsi with the finding of alternative transcripts and microsatellite in the coding region - Baojian Sun; Mingxian Chang; Dali Chen; Pin Nie (Immunogenetics, 2006)

Assessing Impacts of Typhoons and the Chi-Chi Earthquake on Chenyulan Watershed Landscape Pattern in Central Taiwan Using Landscape Metrics - Yu-pin Lin; Tsun-kuo Chang; Chen-fa Wu; Te-chih Chiang; Shin-hwei Lin (Environmental Management, 2006)

Hydrogenation properties of mechanically milled Mg2Ni0.8Cr0.2-CoO/Al2O3 composites - Xiu-li Wang; Jiang-ping Tu; Chang-pin Chen; Xiao-bin Zhang; Xin-bing Zhao (Journal of Zhejiang University-SCIENCE B, 2005)

A G-Quadruplex Ligand 3,3′-Diethyloxadicarbocyanine Iodide Induces Mitochondrion-Mediated Apoptosis But Not Decrease of Telomerase Activity in Nasopharyngeal Carcinoma NPC-TW01 Cells - Chung-Pin Li; Jen-Hsin Huang; Ai-Chi Chang; Yi-Mei Hung; Chao-Hsiung Lin; Yee Chao; Shou-Dong Lee; Jacqueline Whang-Peng; Tze-Sing Huang (Pharmaceutical Research, 2004)